Do the European Data Portal Datasets in the Categories Government and Public Sector, Transport and Education, Culture and Sport Meet the Data on the Web Best Practices? - Morgana Carneiro Andrade; Rafaela Oliveira da Cunha; Jorge Figueiredo; Ana Alice Baptista (Data, 2021)
The European Data Portal is one of the worldwide initiatives that aggregates and make open data available. This is a case study with a qualitative approach that aims to determine to what extent the datasets from the Government and Public Sector, Transport, and Education, Culture and Sport categories published on the portal meet the Data on the Web Best Practices (W3C). With the datasets sorted by last modified and filtered by the ratings Excellent and Good+, we analyzed 50 different datasets from each category. The analysis revealed that the Government and Transport categories have the best-rated datasets, followed by Transportation and, lastly, Education. This analysis revealed that the Government and Transport categories have the best-rated datasets and Education the least. The most observed BPs were: BP1, BP2, BP4, BP5, BP10, BP11, BP12, BP13C, BP16, BP17, BP19, BP29, and BP34, while the least observed were: BP3, BP7H, BP7C, BP13H, BP14, BP15, BP21, BP32, and BP35. These results fill a gap in the literature on the quality of the data made available by this portal and provide insights for European data managers on which best practices are most observed and which ones need more attention.